Solving Phosphorus Fertilization-Related Drip Irrigation Emitter Clogging by Adding Mn2+ - Tianyu Xu; Sanlin Bao; Qiuyue Yu; Yu Gao (Agronomy)
Drip irrigation with a fertilizer application could effectively alleviate the soil pollution caused by excessive phosphorus fertilizer. Phosphate fertilizer was dissolved in water and produced a chemical reaction with the ions in irrigation water. The new precipitates were generated, which caused more severe and complex blockage of drip irrigation emitters. Songhua River water was selected as the irrigation water. The experiment investigated the effects of three types of phosphorus fertilizers (urea phosphate, UP; potassium dihydrogen phosphate, PDP; ammonium polyphosphate, APP) and the concentrations (0.2, 0.3, and 0.4 g/L) on the blockage of drip irrigation emitter. The results showed that three types of phosphorus fertilizers intensified the degree of blockage compared with no fertilization, the order from small to large being UP < PDP < APP. The degree of blockage was directly proportional to the concentration of phosphate fertilizer. The system discharge variation ratio (Dra) under UP, PDP, and APP treatments decreased by an average of 6.2~27.7%, 13.8~33.8%, and 21.5~44.6%, respectively. The Christiansen coefficient of uniformity (CU) decreased by an average of 5.9~23.5%, 10.3~27.9%, and 19.1~38.2%. The UP was superior to PDP and APP from the perspective of drip irrigation evaluation indicators. The main reason was that UP reduced the pH value of the water source and inhibited the generation of carbonates. The APP was unable to lower the pH value and had the most serious blockage. The APP was coupled with three concentrations of Mn2+ (1, 2, and 3 mg/L) for drip irrigation, which could optimize the blockage problem and explore the efficacy of Mn2+. The 2 mg/L Mn2+ could maximize the drip irrigation efficiency of the APP. The average increase in Dra and CU was 24.57% and 18.54% macroscopically. Mn2+ could alter the lattice parameters of carbonates and had a certain impact on their size and morphological distribution on a microscopic level. The results showed that fertilization with UP at a concentration of 0.2 g/L did not significantly exacerbate clogging. The drip irrigation effect of Songhua River water combined with 0.2 g/L concentration UP was the best. Moreover, 2 mg/L of Mn2+ was proposed to alleviate the clogging characteristics of APP4. This study could provide reference for improving the efficiency of the Songhua River drip irrigation system.